Evaluation of the POSKetanmu Website Using E-GovQual and Importance Performance Analysis (IPA) - Nur Dinanita; Anita Wulansari; Rafika Rahmawati (Komunitas Dosen Indonesia, 2025)
The rapid advancement of information and communication technology has driven governments to provide digital public services that are efficient, transparent, and user-centered. One such initiative is the POSKetanmu website developed by the Mojokerto Regency Population and Civil Registration Office, aimed at facilitating online processing of population documents. Despite its purpose, the platform still faces several challenges, including difficulties in understanding service procedures, lengthy account verification, and errors in document submission. This study evaluates the quality of the POSKetanmu website using the E-GovQual model, which consists of six dimensions: Ease of Use, Reliability, Trust, Functionality of the Interaction Environment, Information Content and Display, and Citizen Support. To determine service priorities, the Importance–Performance Analysis (IPA) method was employed. Data were collected from 391 valid respondents using a five-point Likert scale. The results reveal an average conformity level of 96% and an overall gap score of –0.17, indicating that performance lags slightly behind user expectations. Indicators located in Quadrant I, particularly RB1–RB4, EU1, and FI2, were identified as priority areas requiring immediate attention. These findings suggest that improvements in system reliability, interface navigation, and interactive features are essential. The integration of E-GovQual and IPA not only provides practical insights for policy-making but also offers a valuable framework for advancing digital government evaluation.